Reshaping Indian food and agricultural policy to meet the challenges and opportunities of globalization - Pinstrup-Andersen, Per (2002)
This is the Seventeenth EXIM BANK Commencement Day Annual Lecture, delivered at the Yashwantrao Chavan Pratishthan, Gen. Jagannath Bhosale Marg, Mumbai, India 400021; Marc J. Cohen, Special Assistant to the Director General of IFPRI, assisted in the preparation of this lecture.